Representações da infância no cinema: ficção e realidade - Lopes, Francisca Rodrigues (2012)
This research examines the representations that the film has made childhood, from the analysis of a corpus of films that have children as protagonist. Based on the instigation of Aumont and Marie when they say that the film camera is an "eye full of intentions," we face the challenge of explaining how the film has "looked" the child, watching in which scenes of child s life he has captured their images and in which scenarios it is shown. Working with the hypothesis that the "look" of the cinema for children is anchored in cultural conceptions, with all that this involves, a literature search was conducted on two fronts: one on the film, which selected authors like Machado, Knigth, Metz, Costa and others, and the other relating to childhood, which included authors such as Aries, Heywood and Rousseau, among others. The corpus consisted of five films, here regarded as exemplary: Cinema Paradiso (Nuovo Cinema Paradiso, Giuseppe Tornatore, Italy, 1988), Ashes Angela's (Angela's Ashes, USA, 1999), Toy prohibited (Jeux Interdits, René Clément, France, 1952), Life is Beautiful (La vita bella, Roberto Benigni, Italy, 1997) and The White Balloon (Badkonake sefid, Jafar Panahi, Iran, 1995). The theoretical and methodological references mobilized in the analysis of the corpus sought support in authors of the cinema as area, as mentioned above, but also in Freudian psychoanalysis, the theories about the history of the child in the West, including that of Aries, as well as the classical philosophies of education, then the Rousseau s included, Benjamin's philosophy of playing, and in works of relevance around the cinematic language. The results points to the necessary reflection on not only the language of cinema and its relationship with the child's world, but to understand that the representations made by the cinema of childhood are cultural representations, and provide other educational opportunities beyond those conventionally introduced by formal education